(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article provides a philosophical analysis of the interrelation between social consciousness and culture in the formation and enhancement of youth thinking. It examines the mechanisms of cultural formation within social consciousness, the transformation of youth cognition, and the emergence of new socio-cultural trends within the global context. As an element of scientific novelty, the article substantiates the importance of the unity of social consciousness and culture in developing youth intellectual and spiritual growth.